Control Mechanisms and Leadership Styles: A Conceptual Framework for Innovation Projects - Lukito-Budi, Andy Susilo (Universitas Negeri Semarang, 2021)
This is a conceptual paper discussing how to undertake innovation in an organization as a project, and the components of the structure and leadership style as factors that support the implementation of the project. It reviews previous research related to organizational, leadership and control theories. It focuses on introducing the role of leadership and control structures into innovation projects. The suggested structure to be adopted is a mixed combination of organic and mechanical structures. This article argues the importance of the existence of a control mechanism to regulate the project; this functions as a set of tools to control the dynamics of the organizational structure in the project. It also reveals transformational leadership as the most suitable leadership style to control and deliver a successful innovation project. At the end, this article proposes several propositions to be tested further in empirical work. Some discussions about optional research methods are also presented.